Epigenetic regulation of GABAergic differentiation in the developing brain - Gao, Juanmei; Luo, Yuhao; Lu, Yufang; Wu, Xiaohua; Chen, Peiyao; Zhang, Xinyu; Han, Lu; Qiu, Mengsheng; Shen, Wanhua (Frontiers in Cellular Neuroscience, 2022)
In the vertebrate brain, GABAergic cell development and neurotransmission are important for the establishment of neural circuits. Various intrinsic and extrinsic factors have been identified to affect GABAergic neurogenesis. However, little is known about the epigenetic control of GABAergic differentiation in the developing brain. Here, we report that the number of GABAergic neurons dynamically changes during the early tectal development in the Xenopus brain. The percentage of GABAergic neurons is relatively unchanged during the early stages from stage 40 to 46 but significantly decreased from stage 46 to 48 tadpoles. Interestingly, the histone acetylation of H3K9 is developmentally decreased from stage 42 to 48 (about 3.5 days). Chronic application of valproate acid (VPA), a broad-spectrum histone deacetylase (HDAC) inhibitor, at stage 46 for 48 h increases the acetylation of H3K9 and the number of GABAergic cells in the optic tectum. VPA treatment also reduces apoptotic cells. Electrophysiological recordings show that a VPA induces an increase in the frequency of mIPSCs and no changes in the amplitude. Behavioral studies reveal that VPA decreases swimming activity and visually guided avoidance behavior. These findings extend our understanding of histone modification in the GABAergic differentiation and neurotransmission during early brain development.